Students’ Disinhibition in Online Communication and the Implications for Foreign Language Pedagogy - Knežević, Ljiljana J.; Topalov, Jagoda P.; Halupka Rešetar, Sabina J. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Research in computer-mediated communication has pointed to online disinhibition effect, i.e., a tendency to interact with less restraint when online than in face-to-face contacts. The current study explores the presence and level of disinhibition in online communication among university students and sets it in the context of synchronous online foreign language learning. To this end, 284 university students who took a course in English as part of their study programs participated in the research. A quantitative approach employing a survey design was adopted and the results were analyzed by means of descriptive and inferential statistical tests in SPSS 25. The findings show that the overall level of online disinhibition is rather low among the participants—the students self-report they feel inhibited when using the internet and communicating online. It also shows that male students tend to be more disinhibited in online communication than females. Two factors, the ability to immerse themselves in online learning surroundings and the use of headphones while attending lessons online are found to produce higher disinhibition levels. The findings imply that the affective domain deserves special attention in creating and conducting online language courses and that the digital environment requires a specific student-centered approach that is yet to be explored and defined.